Should firms allow workers to choose their own wage? - Gary Charness (IZA World of Labor, 2016)
Economists typically predict that people are inherently selfish; however, experimental evidence suggests that this is often not the case. In particular, delegating a choice (such as a wage) to the performing party may imbue this party with a sense of responsibility, leading to improved outcomes for both the delegating entity and the performing party. This strategy can be risky, as some people will still choose to act in a selfish manner, causing adverse consequences for productivity and earnings. An important issue to consider is therefore how to encourage a sense of responsibility in the performing party.
Keywords: B49; C91; D03; J2; J3; 330; delegation; responsibility; social outcomes; experimental evidence